Burnout and Compliance in Filling Out Pre-Anesthesia Report Forms by Anesthesitants - I Nyoman Tripayana; Emanuel Ileatan Lewar; Komang Rosa Tri Anggaraeni; I Nyoman Yoga Diputra (GLOBAL HEALTH SCIENCE GROUP, 2025)
Burnout is a psychological process caused by unrelenting work stress, which indirectly affects the completeness of pre-anesthesia reports. Based on a survey of medical records analysis, surgical anesthesia report forms were still found in medical records that were incomplete. The purpose of this study was to explore preliminary data on the burnout experienced by anesthesiologists and their compliance with filling out anesthesia reports. This study is a qualitative study with a multiple case study design using a descriptive approach. The participants in this study were anesthetists at Klungkung Regional General Hospital, with a total of five participants in the operating room. The data collection method in this study used primary data by conducting interviews on the level of burnout and compliance of anesthetists, as well as assessment sheets of observations regarding compliance in filling out anesthesia report forms. The data analysis techniques used in this study were individual case analysis and cross-case analysis. The level of burnout experienced by anesthesiologists varies across each dimension. Overall, participants tended to experience mild emotional exhaustion. In the depersonalization dimension, participants were found to be in the severe category. Meanwhile, in the self-efficacy dimension, all three participants were in the low category. The pre-anesthesia assessment form contained items that were not filled in, namely those related to lifestyle history. Burnout, especially when influenced by work fatigue and psychosocial stress, has the potential to reduce the quality of documentation, which plays an important role in patient safety. Therefore, organizational efforts are needed to reduce burnout through workload management, managerial support, and a more effective documentation system in order to improve compliance and the quality of anesthesia services.